Encapsulation of anthocyanins from bilberries – Effects on bioavailability and intestinal accessibility in humans. (15th May 2018) - Mueller, Dolores; Jung, Kathrin; Winter, Manuel; Rogoll, Dorothee; Melcher, Ralph; Kulozik, Ulrich; Schwarz, Karin; Richling, Elke
Highlights: A human pilot intervention study was performed with volunteers with and without a colon. Anthocyanins/bilberry extract was stabilized by whey protein or citrus pectin. Whey protein encapsulation modulated short-term bioavailability. Citrus pectin encapsulation increased intestinal accessibility during passage through the small intestine. The degradation product phloroglucinol aldehyde was present in plasma. Abstract: Anthocyanins are flavonoids that have been suggested to provide beneficial health effects. The biological activity of anthocyanins is influenced by their pharmacokinetic properties, but anthocyanins are associated with limited bioavailability in humans. In the presented study, we investigated how the encapsulation of bilberry extract (BE), a source of anthocyanins, with either whey protein or citrus pectin influences the bioavailability and intestinal accessibility of anthocyanins in humans. We performed an intervention study that analyzed anthocyanins and their degradation products in the urine, plasma, and ileal effluent of healthy volunteers and ileostomists (subjects without an intact colon). We were able to show, that whey protein encapsulation modulated short-term bioavailability and that citrus pectin encapsulation increased intestinal accessibility during passage through the small intestine and modulated the formation of the degradation product phloroglucinol aldehyde (PGAL) in human plasma.